Socioeconomic determinants of food security and dietary quality in ecuadorian agricultural communities: A comparative analysis - Baldeón-Báez, Sandra; Ronquillo, Ángel; Montaño, Maluvé; Contreras-Vásquez, Luis; Franco-Crespo, Christian (Progress in Nutrition, 2025)
Background and aim: Malnutrition, encompassing both undernutrition and overnutrition, remains a critical public health issue in Ecuador, particularly in agricultural communities. This study aims to analyse the dietary quality and diversity of agricultural households while examining the socioeconomic factors that shape nutrition across three regions: the provinces of Guayas and Cotopaxi, and the parish of San Mateo in Esmeraldas. Methods: Using data from 24-hour dietary recalls and socioeconomic surveys from a sample of 102 households, this research employs statistical tools, including ANOVA and Kruskal-Wallis tests, to identify key differences in dietary patterns. Results: The findings reveal significant regional disparities in food consumption, driven primarily by income, education, and employment. Households in Milagro, with an average income of 1,650, reported greater dietary diversity compared to San Mateo (250) and Salcedo (550), indicating that higher income allows for access to a wider range of food groups. These results underscore the crucial role of socioeconomic status in determining dietary choices and nutritional adequacy. Conclusions: The study highlights the importance of targeted interventions, including improving food accessibility, promoting nutritional education, and supporting small-scale farmers. Addressing these regional and socioeconomic disparities is essential to mitigating malnutrition in Ecuador. By focusing on socioeconomic drivers of dietary quality, this study provides valuable insights for policymakers aiming to develop region-specific strategies that promote food security, improve nutrition, and support sustainable agricultural practices, contributing to Ecuador’s broader public health and development goals.